Bryophyte Flora of AlUla County (Saudi Arabia)—Distribution, Ecology, and Conservation - Vincent Hugonnot; Florine Pépin; Jan Freedman (Plants)
Intensive surveys recently conducted in AlUla County (northwest Saudi Arabia) have made it possible to compile an exhaustive list of the forty-eight bryophyte species (six liverworts and forty-two mosses) known in this region and compare it with an updated checklist of bryophytes from Saudi Arabia, which now counts 31 liverworts and 135 mosses. The ecology, taxonomy, and distribution of each taxon are provided and discussed in a systematic catalog. Although particularly arid and lacking permanent watercourses, AlUla County has proven to be surprisingly rich in bryophytes. Some remarkable species are even confined here, such as Riella affinis, Acaulon triquetrum, Microbryum rectum, and Syntrichia rigescens. Two endemic species were also observed. An updated checklist of Arabian bryophyte endemics is provided. Specific recommendations regarding the conservation of bryophyte heritage are outlined.